Renal ultrasonographic anatomy in dogs and cats - Canpolat, Ibrahim (Scientific and Technical Research Council of Turkey, 1996)
Ultrasonographic examination was conducted in adult healty dogs and cats by using 3.5-5 Mhz convex transducers. Longitudinal and transversal sections were obtained in left and right kidneys, renal image lenght, morphological structure and echogenite difference were examined. Renal capsule hyperechogen, renal sinus echogen, cortex and mudulla hypoechogen were imaged dogs and cats. In these study, renal Ultrasonographic image and anatomical measurement of normal renal parameters were obtained. These finding is to be useful to diagnose kidney associated disease of dogs and cats.
Köpek ve Kedilerde Böbreklerin Ultrasonografik Anatomisi
Keywords: Dog and cat; Kidney; Ultrasonography